Making Pupuk Lindi at Al-Ittihad School Pekanbaru : Pembuatan Pupuk Lindi Di Sekolah Al-Ittihad Pekanbaru - Nurliana Nasution; Jeni Wardi; Nurhayani Lubis (Institut Riset dan Publikasi Indonesia, 2023)
This service was held on Monday, July 31 2023. This service was held at Al Ittihad School Pekanbaru. The training participants were 17 high school students, this service ran smoothly and all participants were able to take part in the training well. In this service activity, participants are given a questionnaire before and after the training. The results of questionnaires before and after training showed a significant increase in knowledge regarding fertilizer making. The school also really supports this service activity, so that with the support of all parties the service runs well and is successful.